Enhancing Car Service Efficiency: Shee Auto Polish & Ceramic Coating’s Online Booking System Development (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Car owners face the challenge of finding convenient and efficient car wash services in San Vicente, Alaminos City. Among them, Shee Auto Polish & Ceramic Coating stands out, but its manual appointment booking process often leaves customers frustrated with long wait times and scheduling conflicts. This research introduces a system architecture for a digital platform facilitating car wash appointments at Shee Auto Polish & Ceramic Coating. It aims to address inefficiencies observed in the conventional manual booking method. A solid foundation for comprehending the background and complications behind the development of the car wash booking system is provided by the study’s framework, which is enhanced by the incorporation of ideas from relevant literature. To obtain data from respondents, the researchers utilized a range of data collection methods, such as questionnaires for surveys, in-person interviews, internet searches, document analysis, and observation. The system facilitates customer and employee workflow, improves overall happiness and convenience for the shop and for the community, and offers a user-friendly interface in the system for better usage, effective data management, and improved service delivery for the car wash facility. As Shee Auto Polish & Ceramic Coating anticipates more vehicles, developing an efficient online booking system becomes crucial for improving customer service and operational efficiency.